Synthesis of nano-octahedral MgO via a solvothermal-solid-decomposition method for the removal of methyl orange from aqueous solutions. Issue 18 (13th March 2020) - Yan, Xirui; Tian, Zixin; Peng, Wencai; Zhang, Jianshu; Tong, Yanbin; Li, Jun; Sun, Dekui; Ge, Hui; Zhang, Jinli
Abstract : This article reports a facile nano-octahedral MgO synthetic method and its adsorption performance for methyl orange. Abstract : Nano magnesium oxide has wide applications, and MgO with (111) facets has wider potential applications than MgO with (100) facets ( e.g., in catalysis and adsorption). However, nano MgO with (111) polar faces has not been studied throughly, so the preparation of nano-octahedral MgO (N-O-MgO) with eight exposed (111) facets remains a great challenge. Herein, we successfully synthesised N-O-MgO via an effective solvothermal-solid-decomposition method and studied its adsorption performance. The obtained N-O-MgO showed excellent performance (229.36 mg g −1 ) for methyl orange (MO). The adsorption follows the pseudo-second-order kinetic equation and the Langmuir isotherm model. The dimensionless parameter R L (0.042) and Gibbs free energy Δ G (−6.538 kJ mol −1 ) revealed that the adsorption of MO on N-O-MgO was a spontaneous and feasible process. The adsorption of MO and methyl blue (MB) on N-O-MgO were studied to determine the adsorption sites. Based on these experiments and analysis, it was determined that the adsorption sites were magnesium ions and the adsorption mechanism was proposed to describe the adsorption process.